2021
DOI: 10.1111/ijcp.14486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors and age‐related sexual and erectile dysfunction in patients with inflammatory bowel disease: A tertiary centre experience

Abstract: Introduction The impact of sexuality and quality of life (QOL) is one of the main concerns of IBD. Despite the obvious relevance of this problem, knowledge of the extent of sexual dysfunction (SD) in IBD is limited. Aim of this study was to assess the prevalence of SD and erectile dysfunction (ED), QOL their predictors, and their age‐related dynamic in IBD patients. Methods In this cross‐sectional study, 202 IBD patients [122 male, 80 female, 133 Crohn's disease (CD), 69 ulcerative colitis (UC)] fulfilled Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The relationship between IBD and ED remains enigmatic in existing literature. Some studies suggest no signi cant correlation between IBD and ED [28,29], while others indicate a positive correlation between IBD and the risk of ED [30,31]. Nonetheless, our research ndings show a clear causal relationship between Crohn's disease and ED, while ulcerative colitis doesn't exhibit a signi cant causal relationship with ED.…”
Section: Discussioncontrasting
confidence: 52%
“…The relationship between IBD and ED remains enigmatic in existing literature. Some studies suggest no signi cant correlation between IBD and ED [28,29], while others indicate a positive correlation between IBD and the risk of ED [30,31]. Nonetheless, our research ndings show a clear causal relationship between Crohn's disease and ED, while ulcerative colitis doesn't exhibit a signi cant causal relationship with ED.…”
Section: Discussioncontrasting
confidence: 52%
“…This literature review highlights the multifaceted sexual di culties women who live with IBD have, such as painful intercourse, vaginismus, lower sexual satisfaction and desire and di culty with orgasm [13,[18][19][20][21][22][23]. The literature also highlights that there is a bidirectional relationship between depression and sexual dysfunction [16,17] which has been described in the broader literature by Velten and Milani [37].…”
Section: Discussionmentioning
confidence: 95%
“…Shmidt et al [23] found in the United States of America, 97% of 116 women participants across all age groups reported sexual dysfunction, which the authors explained was 47% higher than the general population. In the study conducted by Nisihara and colleagues [13] in Brazil, 82.5% of the 40 women participants reported sexual dysfunction and a Croatian study found that 75% of the 80 women who completed the FSFI had sexual dysfunction [20].…”
Section: Ibd and Sexual Functioningmentioning
confidence: 97%
“…Both problems were highest among 21–30-year-olds, increasing after 51 years of age. In multivariate analysis, significant predictors of sexual problems in men were CD phenotype, disease duration, and the emotional domain of the QoL questionnaire (IBDQ), while depression, emotional, and bowel domains of the IBDQ were strongly associated with erectile dysfunction [ 36 ]. Similarly to a study on female patients, CD (not UC) was associated with sexual dysfunction.…”
Section: Sexual Problems In Male Patients With Ibdmentioning
confidence: 99%